WOUND PATTERNS OF GENITAL INJURY IN FEMALE SEXUAL ASSAULT VICTIMS IN RS BHAYANGKARA TK II MEDAN 2018 2019 - Tanjung, Khofifah Indrawati; Gafar, Abdul (Medicina Biomedica Journal, 2023)
Background: Cases of sexual violence, namely rape, are still happening. We can see this with information from various print media, electronic media and mass media. Rape cases often cause deep trauma or scars on the victim's body which can be used as evidence. Objective: To determine the pattern of genital wounds of women victims of rape in hospital. Bhayangkara TK.II Medan from 2018-2019. Methods: This study used a descriptive method with a retrospective approach based on the results of secondary data from post mortem et repertum in cases of rape at the Hospital of Bhayangkara TK.II Medan which were taken by total sampling. Result: It was found that the victims with the most data were aged 12-16 years, as many as 96 victims (46.2%) who had torn wounds and were located in Hymen as many as 201 victims (91.4%), with the direction of hymen tears at 6 o'clock as many as 152 victims (11.6%). Conclusion: Teenagers with tearing wounds in the hymen position at 6 o'clock are most victims of rape.